GR_GERICHTE ZK1 2020 136 vom 8. Oktober 2020 , fürsorgerische Unterbringung und Behandlung ohne Zustimmung - GR Gerichte (2020)
fürsorgerische Unterbringung und Behandlung ohne Zustimmung | KES Fürsorgerische Unterbringung